Makna Pernikahan Ta’aruf Berdasarkan Surat Al-Nisa ayat 1 di Desa Tiangau Siantan Selatan Kepulauan Anambas - Emmy Solina; Rahma Syafitri; Novi Novi (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
Ta'aruf is interpreted as the application process for prospective grooms and prospective brides before they carry out the marriage proposal (Khitbah). Usually, people whose marriages were carried out previously with the taaruf process are only in certain circles, for example the Islamic  boarding school students (santri) or the religious scholars. However, the taaruf phenomenon has also developed and expanded to all levels of society, even to remote villages. One of them is the Tiangau village community who choose to marry through ta'aruf. The research method used in this study is a qualitative method with a descriptive approach. Data collection techniques used are interviews, observation and documentation. The informant selection technique was purposive sampling which determined informants based on criteria that were able to answer the formulation of the problem, namely taaruf actors, ustad who became a liaison for taaruf and the Tiangau village community. As for data analysis through data reduction, data presentation and drawing conclusions. The results of the study are the meaning of ta'aruf marriage in the Tiangau community, namely ta'aruf marriage as the implementation of the teachings of Islamic law, ta'aruf marriage as a medium for couples to get to know each other, and as obedience to God Almighty. The meaning of taaruf is also in accordance with the meaning of the letter Annisa verse 1 which states about please help and love your partner. This means that getting to that stage starts with getting to know each other (ta'aruf) between men and women with the intention that marriage will be a good way.